Comparison of the effectiveness and pregnancy outcomes of labor induction with dinoprostone or single-balloon catheter in term nulliparous women with borderline oligohydramnios. Issue 6 (20th March 2022) - Zhang, Yongqing; Chen, Luping; Yan, Guohui; Zhou, Menglin; Chen, Zhengyun; Liang, Zhaoxia; Chen, Danqing
Abstract: Backgrounds: At present, there is no consensus on the induction methods in term pregnancy with borderline oligohydramnios. This study aimed to compare the effectiveness and pregnancy outcomes of labor induction with dinoprostone or single-balloon catheter (SBC) in term nulliparous women with borderline oligohydramnios. Methods: We conducted a retrospective cohort study from January 2016 to November 2018. During the study period, a total of 244 cases were enrolled. Of these, 103 cases were selected for induction using dinoprostone and 141 cases were selected for induction with SBC. The pregnancy outcomes between the two groups were compared. Primary outcomes were successful vaginal delivery rates. Secondary outcomes were maternal and neonatal adverse events. Multivariate logistic regression was used to assess the risk factors for vaginal delivery failure in the two groups. Results: The successful vaginal delivery rates were similar between the dinoprostone group and the SBC group (64.1% [66/103] vs . 59.6%, [84/141] P  = 0.475), even after adjustment for potential confounding factors (adjusted odds ratio [aOR]: 1.07, 95% confidence interval [CI]: 0.57–2.00, P  = 0.835). The incidence of intra-amniotic infection was lower in the dinoprostone group than in the SBC group (1.9% [2/103] vs . 7.8%, [11/141] P  < 0.001), but the presence of non-reassuring fetal heart rate was higher in the dinoprostone group than in the SBC group (12.6% [13/103] vs . 0.7%, [1/141] P  < 0.001). Multivariate logistic regression showed that nuchal cord was a risk factor for vaginal delivery failure after induction with dinoprostone (aOR: 6.71, 95% CI: 1.96–22.95). There were three factors related to vaginal delivery failure after induction with SBC, namely gestational age (aOR: 1.51, 95% CI: 1.07–2.14), body mass index (BMI) >30 kg/m 2 (aOR: 2.98, 95% CI: 1.10–8.02), and fetal weight >3500 g (aOR: 2.49, 95% CI: 1.12–5.50). Conclusions: Term nulliparous women with borderline oligohydramnios have similar successful vaginal delivery rates after induction with dinoprostone or SBC, with their advantages and disadvantages. In women with nuchal cord, the risk of vaginal delivery failure is increased if dinoprostone is used in the induction of labor. BMI >30 kg/m 2, large gestational age, and estimated fetal weight >3500 g are risk factors for vaginal delivery failure after induction with SBC.